Cranioplasty outcomes and associated complications: A single-centre observational study. (2nd January 2016) - Liang, Ee Shern; Tipper, Geoffrey; Hunt, Lyn; Gan, Peter Yee Chiung
Abstract : Introduction. The resurgence of decompressive craniectomy has led to recent published reviews of the safety of cranioplasties. To date there is a wide range of reported mortality and morbidity. This observational study reports the outcomes of the cranioplasty operations from a single centre and evaluates the factors involved in their management. Methods. A retrospective search of all theatre logs was performed for the years 2006–2013 inclusive. 88 operations were documented as 'Cranioplasty'. Data collection include patient demographics, type of cranioplasty used, time lapse between decompression and cranioplasty, seniority of the operating surgeon(s), antibiotic regimen and complications. Outcomes were recorded at the three-month follow-up. Results. The overall complication rate was 6.8%. The mean patient age was 36.2 years. 52.2% of patients had decompressive craniectomy for trauma, 11.3% had infectious pathology, 9% had subarachnoid haemorrhage, 9% had tumour with bone infiltration and 3.4% had stroke. 55.7% of patients had cranioplasty within 6 months of craniectomy. 61.3% of cranioplasties were with autologous bone, 20.4% titanium, 10.2% acrylic and 7.9% polyetheretherketone (PEEK). Significant complications included one case of infection, two cases of subgaleal haematoma and one extradural collection. No deaths were noted. No correlation was found between infection and the use of drains. 68.6% of cases were done by either a senior surgeon or a supervised registrar. There was an observable difference in complication rates in relation to the seniority and experience of the operator. However, patient numbers and complications were insufficient to achieve statistical significance. Strict antimicrobial prescribing was observed. Conclusion. Some potentially preventable complications have been addressed with a resulting rate of complications lower than other published reports. We use two standard adjuncts: the presence of a senior surgeon and strict antimicrobial regimens. We believe that our results could be transferrable to other units by following similar guidelines.